Spatial-temporal analysis of the risk to water pollution against land use changes in Lobo Stream Drainage Basin, Itirapina-SP, Brazil - Anjinho, Phelipe da Silva; Santos, Allita Rezende dos; Barbosa, Mariana Abibi Guimarães Araujo; Mauad, Frederico Fabio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The landscape transformation caused by economical activities generates impacts on natural ecosystems and the water system is one of the most susceptible to anthropic alterations. In this context, the objective of this study was to analyze the vulnerability of the water resources of the Lobo Stream Drainage Basin (LSDB), Itirapina-SP, through the application of the Environmental Quality Index of Water Resources (EQI-Hydro), in a 32 years period, corresponding to the years 1985 and 2017. The EQI-Hydro was calculated from the analysis of the Euclidean distance of the water resources to the impacting sources, determined by means of land use classification, and then rescaled based on fuzzy logic. The results show that approximately 57% of the watershed area is classified as high and very high EQI-Hydro. The Itaqueri River and the Água Branca Stream are the most vulnerable to pollution due to their proximity to pollution sources. This manifests the need for adequate agricultural practices and public policies for forest restoration, aiming the preservation of the LSDB water resources.